IMPLEMENTASI QUALITY FUNCTION DEPLOYMENT (QFD) PADA PROSES SELF ENTRY MATA KULIAH DI FAKULTAS BISNIS DAN EKONOMIKA UNIVERSITAS SURABAYA - Flaurensia Pamela Sumarman (Perpustakaan Universitas Surabaya, 2015)
In order to upgrade the quality of services at the process of self-entry courses in the Faculty of Business and Economics, University of Surabaya, the research done by implementing the Quality Function Deployment (QFD). The purpose of the implementation of the Quality Function Deployment (QFD) in the process of self-entry course is to get the Voice of the Customer, Priority Technical Response Actions, as well as strategies that resulted in the proposal should be taken by the company to improve the quality of the process of self service entry courses. Based on research conducted using the method of Quality Function Deployment (QFD), obtained attributes are a priority to improvement of quality of service (self‐entry process execution time courses, servers that are used to make the process of self‐entry courses, and classroom courses parallel) , and the measures proposed by the company technical response (increase the bandwidth capability, determination of parallel class, and the addition of parallel class courses). From the calculations, it can be seen that all the technical response from the company yet again the maximum and needs to be improved, in order to improve the quality of the process of self service entry in the Faculty of Business and Economics, University of Surabaya.